Investment Policy of The Kottarakara Co-Operative Urban Bank in Kollam District of Kerala State - Kannan. V. Unnithan AND M. Somasundaram (International Journal for Research in Engineering Application & Management, 2018)
The present paper presents the investment policy of The Kottarakara Co-operative Urban Bank (KCUB) in Kollam district of Kerala state. Firstly, to briefly list out the types of permissible investment such as issues of securities, treasury bills, SLR &non-SLR bonds, term deposits, etc. Secondly, to describe the bank investments by way of investments in securities, purchase of government securities, parameters for investment and funds of the bank. Thirdly, to point out the procedure for investments adopted in the KCUB such as investment in primary market, purchase of government securities in secondary market and sale of government securities. Fourthly, to suggest briefly the delegations of powers for investment/purchase/sale of securities. Fifthly, to list out the reporting of transactions by way of daily report, monthly report, quarterly report and half yearly report. Finally, to discuss about the categorisation of investments like held to maturity, held for trading and available for sale. The present study is helpful to the account holders and guidance’s to all employees & employers in The Kottarakara Co-operative Urban Bank.